2023
DOI: 10.3390/ijms241512425
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant and Anxiolytic Effects of L-Methionine in the WAG/Rij Rat Model of Depression Comorbid with Absence Epilepsy

Abstract: Depression is a severe and widespread psychiatric disease that often accompanies epilepsy. Antidepressant treatment of depression comorbid with epilepsy is a major concern due to the risk of seizure aggravation. SAMe, a universal methyl donor for DNA methylation and the synthesis of brain monoamines, is known to have high antidepressant activity. This study aimed to find out whether L-methionine (L-MET), a precursor of SAMe, can have antidepressant and/or anxiolytic effects in the WAG/Rij rat model of depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…It has been shown that a decrease in the activity of the dopamine system in the mesolimbic region of the brain is linked to both absence seizures and depression-like symptoms in WAG/Rij rats ( Birioukova et al, 2005 ; Sarkisova et al, 2022 ; Fedosova et al, 2023 ). Administering mixed dopamine D1/D2 receptor agonists systemically led to a decrease in SWDs and comorbidity with depression-like symptoms in WAG/Rij rats ( Midzianovskaia et al, 2001 ; Sarkisova et al, 2023 ). Conversely, dopamine antagonists enhanced the occurrence of SWDs and depression-like behavioral symptoms in these rats ( Sarkisova et al, 2008 , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that a decrease in the activity of the dopamine system in the mesolimbic region of the brain is linked to both absence seizures and depression-like symptoms in WAG/Rij rats ( Birioukova et al, 2005 ; Sarkisova et al, 2022 ; Fedosova et al, 2023 ). Administering mixed dopamine D1/D2 receptor agonists systemically led to a decrease in SWDs and comorbidity with depression-like symptoms in WAG/Rij rats ( Midzianovskaia et al, 2001 ; Sarkisova et al, 2023 ). Conversely, dopamine antagonists enhanced the occurrence of SWDs and depression-like behavioral symptoms in these rats ( Sarkisova et al, 2008 , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Administering mixed dopamine D1/D2 receptor agonists systemically led to a decrease in SWDs and comorbidity with depression-like symptoms in WAG/Rij rats ( Midzianovskaia et al, 2001 ; Sarkisova et al, 2023 ). Conversely, dopamine antagonists enhanced the occurrence of SWDs and depression-like behavioral symptoms in these rats ( Sarkisova et al, 2008 , 2023 ). The basal ganglia regulate absence seizures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations